The Determinant of HIV Testing on Housewives in The Pesisir Jember Area - Ida Nurmawati; Ervina Rachmawati; Faiqatul Hikmah (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
The development of HIV / AIDS cases in Jember Regency from year to year also tends to increase, but people who take HIV tests have decreased. Most cases of HIV / AIDS are in the "Golden Triangle" Subdistrict, namely Puger, Kencong, and Gumukmas which are the coastal areas of Jember. Objective: to determine the predisposing factors, enabling, reinforcing housewives in the implementation of HIV testing. Methods: This research was an analytical survey with a cross-sectional approach to proving the research hypothesis in the form of a correlation and influence together with the predisposing, enabling, and reinforcing factors of housewives on the implementation of HIV testing. The population was all housewives in Kencong sub-district and the study sample was 96 households. The sample collection technique used quota sampling and data collection were carried out by giving questionnaires to housewives who visited to Public Health Center of  Kencong. Data analysis using chi-square test and logistic regression test. Results: The results showed that there was correlation between age (p = 0.042), education (p = 0.0001), knowledge (p = 0.025), access to HIV testing services (p = 0.025), husband's support (p = 0.019), support from friends. (p = 0.002), health care support (p = 0.001) and there is a co-effect of age (p = 0.046; ExpB = 2.531), education (p = 0.001; ExpB = 4.620), access to HIV testing services (p = 0.041; ExpB = 3,928) on the implementation of HIV testing at Public Health Center of Kencong. Conclusion: There is a co-effect of the housewife's age, housewife education, and access to HIV testing services on the implementation of HIV testing at the Public Health Center of  Kencong. Empowerment of productive age housewives as peer cadres for HIV / AIDS promotion and HIV testing. Abstrak: Perkembangan kasus HIV/AIDS Kabupaten Jember dari tahun ke tahun juga cenderung meningkat, namun orang yang melakukan tes HIV mengalami penurunan. Kasus HIV/AIDS terbanyak berada pada Kecamatan “Segi Tiga Emas” yaitu Puger, Kencong, dan Gumukmas yang meruapakn daerah pesisir Jember. Tujuan: mengetahui faktor predisposing, enabling, reinforcing ibu rumah tangga dalam pelaksanaan tes HIV. Metode: Penelitian ini merupakan survei analitik dengan pendekatan waktu crossectional untuk membuktikan hipotesis penelitian berupa ada hubungan dan pengaruh secara Bersama-sama factor predisposisi, pemungkin, dan penguat ibu rumah tangga terhadap pelaksanaan tes HIV. Populasi adalah seluruh ibu rumah tangga di kecamatan Kencong dan sampel penelitian sebesar 96 IRT. Teknik pengumpulan sampel menggunakan quota sampling dan pengumpulan data dilakukan dengan pemberian angket kepada ibu rumah tangga yang berkunjung ke Puskesmas Kencong. Analisis data menggunakan uji chi square, dan uji regresi logistic. Hasil: Hasil penelitian diketahui ada hubungan usia (p=0,042), pendidikan (p=0,0001), pengetahuan (p=0,025), akses layanan tes HIV (p=0,025), dukungan suami (p=0,019), dukungan teman (p=0,002), dukungan nakes (p=0,001) serta ada pengaruh secara bersama-sama usia (p=0,046; ExpB=2,531), pendidikan (p=0,001; ExpB=4,620), akses layanan tes HIV (p=0,041; ExpB=3,928) terhadap pelaksanaan tes HIV di Puskesmas Kencong. Kesimpulan: Ada pengaruh secara bersama-sama usia IRT, Pendidikan IRT, dan akses layanan tes HIV terhadap pelaksanaan tes HIV di Puskesmas Kencong. Pemberdayaan IRT usia produktif sebagai kader teman sebaya untuk promosi HIV/AIDS dan tes HIV.